CdS Decorated on Hierarchically Structured Single Crystal TiO2 Nanosheets for Enhanced Photoelectrochemical H-2 Generation - Raza, Waseem; Kerketta, Ujjaval; Hwang, Imgon; Schmuki, Patrik (ChemElectroChem, 2022)
Single crystal anatase TiO2 nanosheets (TNS) were grown on a fluorine-doped tin oxide (FTO) substrate and then modified via multiple TiCl4 treatments to produce a hierarchical TiO2 structure. This high surface area hierarchical structure was then decorated with CdS (as a visible light absorber) using SILAR treatments. The resulting photoanodes provide a greatly enhanced photoelectrochemical H-2 generation capability. For the optimized TiO2 and CdS decorated TNS electrode, a photocurrent magnitude of 3.5mA/cm(2) at 0.5V Ag/AgCl (under AM 1.5G, 100mW/cm(2)) was obtained, and an applied bias to photoconversion efficiency (ABPE) of 2.5% could be reached. The increase in the specific surface was provided by the hierarchical TiO2 structure responsible for the improved performance in comparison to the plain, non-hierarchical electrode with an ABPE=0.8%. Even after particle decoration, the rapid electron flow through the single-crystalline scaffold was maintained. Consequently, the photoanode presented here best integrates in a synergistic manner, a larger surface area, a fast electron transport, and effective visible light harvesting properties.
CRIS-Team WoS Importer:2022-10-21

Grätzel-Type TiO2 Anatase Layers as Host for Pt Single Atoms: Highly Efficient and Stable Photocatalytic Hydrogen Production - Kerketta, Ujjaval; Kim, Hyesung; Denisov, Nikita; Schmuki, Patrik (Advanced Energy Materials, 2023)
Single atoms (SAs) represent not only a new frontier in classic heterogeneous catalysis but are also increasingly investigated as co-catalysts in photocatalytic reactions. In contrast to classic catalysis, many photocatalytic platforms require only a very low SA loading density to reach a saturated photocatalytic activity. As a result, an optimized light harvesting/carrier transport combination in the supporting semiconductor becomes the key aspect for the overall photocatalytic efficiency. In this work, it is demonstrated that Grätzel type mesoporous TiO2 layers represent an ideal host for Pt single-atoms (SAs) that allow for a highly effective photocatalytic H2 generation. Using a layer with an optimized geometry, structure, as well as Pt SA loading, a photocatalytic H2 production is achieved of up to ≈2900 µL h−1 (under irradiation at λ = 365 nm and I = 65 mW cm−2) – a performance that is far superior to previous Pt SA/TiO2 structures based on TiO2 nanotubes, nanosheets, or metal organic frameworks. Moreover, such SA/substrate combination provides a highly stable H2 production over time. The present work thus introduces the use of this classic TiO2 nanostructure as the most effective host for Pt SAs and its use for highly efficient photocatalytic H2 production from aqueous solutions.
CRIS-Team Scopus Importer:2023-12-08
Keywords: mesoporous titanium dioxide; photocatalytic hydrogen production; Pt single atoms

Room Temperature Hydrogen Gas Sensing Using Zn2TiO4Thin Film - Kerketta, Ujjaval; Daniel, Thomas T.; Yadav, Vimal Kumar Singh; Paily, Roy P. (IEEE Sensors Letters, 2023)
Zn2TiO4 thin film is formed on Si/SiO2 substrate by a spin coating process and Al is used as electrodes. This device has excellent hydrogen (H2) gas sensing properties. The phase and crystal structure of the thin film was studied using X-ray diffraction. The sensor responds linearly at room temperature to H2 gas concentrations ranging from 50 to 250 ppm and shows a good sensitivity toward low ppm of H2. The response time of the sensor is about 76 s at 250-ppm H2. We could fit the sensor response to the Langmuir adsorption model.
CRIS-Team Scopus Importer:2023-03-03
Keywords: gas sensor; hydrogen; room temperature; Sensor materials; Zn

Single-Atom Co-Catalysts Employed in Titanium Dioxide Photocatalysis - Kerketta, Ujjaval; Tesler, Alexander; Schmuki, Patrik (Catalysts, 2022)
With a distinct electronic structure and unsaturated coordination centers, supported single-atoms (SAs) have shown great potential in heterogeneous catalysis due to their superior activity, stability, and selectivity. Over the last few years, the fascination of SA-use spread also over photocatalysis, i.e., a particular case of heterogeneous catalysis in which chemical reactions are activated by charge transfer from an illuminated semiconductor. Titanium dioxide (TiO2) is one of the most studied photocatalytic materials. It is widely used as a light absorbing semiconductor decorated with metallic (nanoparticles and single-atom) co-catalysts. In the current review, we emphasize the role of SAs as a co-catalyst in photocatalysis, and clearly set it apart from the use of single atoms in classic heterogeneous catalysis. The review first briefly describes the principal features of SAs, and gives an overview of most important examples of single-atom co-catalysts. Then, we discuss photocatalysis and key examples of single-atom co-catalysts used on TiO2 photocatalysts and their applications. At last, we provide an outlook for further exploring TiO2-based single-atom photocatalytic systems.
CRIS-Team WoS Importer:2022-11-04